Single Nucleus RNA Sequence (snRNAseq) Analysis of the Spectrum of Trophoblast Lineages Generated From Human Pluripotent Stem Cells in vitro - Khan, Teka; Seetharam, Arun S.; Zhou, Jie; Bivens, Nathan J.; Schust, Danny J.; Ezashi, Toshihiko; Tuteja, Geetu; Roberts, R. Michael (Frontiers in Cell and Developmental Biology, 2021)
One model to study the emergence of the human trophoblast (TB) has been the exposure of pluripotent stem cells to bone morphogenetic protein 4 (BMP4) in presence of inhibitors of ACTIVIN/TGFB; A83–01 and FGF2; PD173074 (BAP), which generates a mixture of cytotrophoblast, syncytiotrophoblast, and cells with similarities to extravillous trophoblast. Here, H1 human embryonic stem cells were BAP-exposed under two O2 conditions (20% and 5%, respectively). At day 8, single nuclei RNA sequencing was used for transcriptomics analysis, thereby allowing profiling of fragile syncytial structures as well as the more resilient mononucleated cells. Following cluster analysis, two major groupings, one comprised of five (2,4,6,7,8) and the second of three (1,3,5) clusters were evident, all of which displayed recognized TB markers. Of these, two (2 &3) weakly resembled extravillous trophoblast, two (5 & 6) strongly carried the hallmark transcripts of syncytiotrophoblast, while the remaining five were likely different kinds of mononucleated cytotrophoblast. We suggest that the two populations of nuclei within syncytiotrophoblast may have arisen from fusion events involving two distinct species of precursor cells. The number of differentially expressed genes between O2 conditions varied among the clusters, and the number of genes upregulated in cells cultured under 5% O2 was highest in syncytiotrophoblast cluster 6. In summary, the BAP model reveals an unexpectedly complex picture of trophoblast lineage emergence that will need to be resolved further in time-course studies.